THE MODEL OF CULTIVATION, INNOVATION, AND MARKETING MODULE DEVELOPMENT: A CASE STUDY ON ‘BAWING’ HERB IN EAST MALAYSIA - Halina Sendera Mohd Yakin; Anna Lynn Abu Bakar; Noorafini Kassim (PEOPLE: International Journal of Social Sciences, 2025)
The uniqueness of ‘bawing’ coupled with the declining involvement among youth, the contemporary national agenda and the scarcity of module development model related to the agricultural sector have sparked the research idea. This paper is inspired to explicate the development of modules on cultivation, innovation and marketing of an herbal plant that is synonymous with the Sabahan of East Malaysia, namely ’bawing’. The modules were developed based on a questionnaire analysis on KASA (Knowledge-Attitude-Skill-Aspiration) aspects rooted in three learning domains, namely cognitive, affective and psychomotor (CAP) as well as contributing factors pertaining to the challenges of fostering a commercial agricultural culture among the community. The development and combination of the 3-in-1 modules is relevant and significant as ’bawing’ possesses countless commercial benefits that are not confined to gastronomic and culinary aspects only. The modules can be utilized in various activities such as Knowledge Transfer Programme (KTP), Teaching of Trainers (ToT), Research and Development (R&D), Teaching & Learning as well as the production of bawing-based prototypes or products. Based on the combination and improvisation of ADDIE and SMDM models as well as SPSS analysis, a model pertaining to the module development process involving four main phases is designed. The Cultivation, Innovation and Marketing Module Development Model (MCIM) which focuses on ’bawing’ herb is suitable for modules development purposes inspired to assess the success of KTP or other similar program particularly those that are affiliated with social transformation aspects as well as cultivation of commercial agricultural culture.